2023
DOI: 10.1186/s13620-023-00237-w
|View full text |Cite
|
Sign up to set email alerts
|

Rate of obesity within a mixed-breed group of horses in Ireland and their owners’ perceptions of body condition and useability of an equine body condition scoring scale

Abstract: Background Equine obesity is a significant health and welfare concern. The proportion of domestic horse populations that are overweight are as high as 45%. As the primary decision-makers for their horses’ care, owners are theoretically ideally placed to identify whether their horses are appropriately conditioned, however, research in other countries has shown that many owners are unable to accurately judge their horse’s body condition. In this study, through the comparison of body condition sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Despite this, owners commonly chose to keep their horses over- rather than underweight due to their conflicting perceptions about horse weight. The literature consistently reports that horse owners are not always accurate interpreters of their horses’ body condition, specifically suggesting owners to be worse at identifying over- compared to underweight horses (Wyse et al 2008 ; Potter et al 2016 ; Morrison et al 2017 ; Golding et al 2023 ). This may be related to previous literature reporting the normalisation of overweight horses (Morrison et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, owners commonly chose to keep their horses over- rather than underweight due to their conflicting perceptions about horse weight. The literature consistently reports that horse owners are not always accurate interpreters of their horses’ body condition, specifically suggesting owners to be worse at identifying over- compared to underweight horses (Wyse et al 2008 ; Potter et al 2016 ; Morrison et al 2017 ; Golding et al 2023 ). This may be related to previous literature reporting the normalisation of overweight horses (Morrison et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size required to estimate apparent prevalence with a given precision was calculated. The following formula was used to calculate the sample size: n = (Z 2 Â P(1 À P))/d 2 where n = sample size, Z = statistic for level of confidence (1.96 for a 95% level of confidence), P = expected prevalence of obesity (apparent prevalence) (conservative estimate of 25% based on limited studies), 8,10,11,18 d = delta precision (5% so d = 0.05) the half-width of the CI (error margin). The calculated sample size was 285 ponies.…”
Section: Adrenocorticotropic Hormonementioning
confidence: 99%
“…10 The only study of obesity in horses and ponies in Ireland found that 45.0% of 60 leisure horses and ponies of different breeds were overweight. 11 The aim of this study was to investigate the prevalence of obesity in the popular native Irish Connemara pony breed and to determine if evidence of ID or laminitis in these ponies could be predicted by morphometric (body condition score [BCS], cresty neck score [CNS], regionalised adiposity) or metabolic (triglyceride and glucose concentrations) markers. Since IR at the tissue level was not assessed in this study, increased BIC or an abnormal insulin response post carbohydrate challenge, referred to collectively as hyperinsulinaemia, were used to provide evidence of ID.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Emma Golding and co‐workers in Ireland and Israel investigated the rate of obesity within a mixed‐breed group of horses in Ireland and their owners' perceptions of body condition and useability of an equine body condition scoring (BCS) scale .…”
Section: Equine Obesitymentioning
confidence: 99%